STRATEGI PEMBELAJARAN GURU TERHADAP SISWA SLOW LEARNING AND SISWA SPEED LEARNING DALAM PROSES PEMBELAJARAN SOSIOLOGI DI SMAN Kelas XII IPS2 Se-Kecamatan Pancung Soal Inderapura Pesisir Selatan - Marlina, Yeni - (Pendidikan Sosiologi, 2014)
This research is motivated by how the student teachers learning strategies and student learning slow speed learning in the learning process sociology, this study aimed to describe the learning strategies student teachers and students of slow learning speed of learning in the learning process at SMAN sociology class XII IPS2 Se-District of Problem beheaded Inderapura the South Coast. The approach used in this study is a qualitative approach. and descriptive informants of this study was sociology teacher and class XII students at SMAN IPS2 Se-District of beheading Problem Inderapura the South Coast. the selection of informants in this study using purposive sampling technique, the type of data used primary data and secondary data. data collection techniques are observation, interviews, documentation search. the unit of analysis is the individual that is the teacher of sociology. data analysis using the principles of Miller and Huberman that includes three phases: (1) data reduction, (2) Presentation of data, (3), Puller conclusion. These results indicate that (a) the student teachers learning strategies and student learning slow speed of learning in the learning process sociology at SMAN 1 beheaded Problem Inderapura South Coastal (1) teacher strategies, discussions (2) strategies of teachers, the questions, (3 ) strategies of teachers, motivation, (4) strategies of teachers, question and answer, (5) strategies of teachers, explaining the material, (6) strategies of teachers, the question is different from the slow child, (7) strategies of teachers, reading a book at home, (8) teacher strategies, arranging appropriate learning material fact, (9) teacher strategies, uncovering opinions, (10) strategies of teachers, learning materials concluded. (b) strategies of teachers to student learning and student learning slow speed of learning in the learning process sociology at SMAN 1 Water Temple, (1) strategies of teachers, assignments, (2) strategies of teachers, guiding students, (3) strategies of teachers, provide reinforcement to the students, (4) strategies of teachers, giving special attention to the students, (5) strategies of teachers, communication with students, (6) strategies of teachers, as well as additional approaches to student learning, (7) strategies of teachers, giving additional duties at home, (8) strategies of teachers, the extracurricular berpartisifasi, (9) teacher strategies, memrpersentasikan material, (10) strategies of teachers, look at the condition of the student.